An Ig Transmembrane Domain Motif Improves the Function of TCRs Transduced in Human T Cells: Implications for Immunotherapy. Issue 4 (May 2019) - D'Apice, Luciana; Cuccaro, Fausta; Varriale, Sonia; Cipria, Deborah; Sartorius, Rossella; Circosta, Paola; Cignetti, Alessandro; Salerno, Massimiliano; Coscia, Maria R.; Oreste, Umberto; Marzullo, Vincenzo M.; Martini, Giuseppe; et al.
Abstract : Adoptive transfer of T lymphocytes (ACT) engineered with T-cell receptors (TCRs) of known antitumor specificity is an effective therapeutic strategy. However, a major constraint of ACT is the unpredictable interference of the endogenous TCR α and β chains in pairing of the transduced TCR. This effect reduces the efficacy of the genetically modified primary T cells and carries the risk of generating novel TCR reactivities with unintended functional consequences. Here, we show a powerful approach to overcome these limitations. We engineered TCR α and β chains with mutations encompassing a conserved motif (FXXXFXXS) required to stabilize the pairing of immunoglobulin heavy chain transmembrane domains. Molecular modeling supported the preferential pairing of mutated TCR and impaired pairing between mutated and wild-type TCRs. Expression of the mutated TCR was similar to wild type and conferred the expected specificity. Fluorescence resonance energy transfer analysis in mouse splenocytes transduced with mutated or wild-type TCRs showed a higher proximity of the former over the latter. Importantly, we show that mutated TCRs effectively outcompete endogenous TCRs and improve in vitro antitumor cytotoxicity when expressed in ex vivo isolated human T cells. This approach should contribute to improving current protocols of anticancer immunetherapy protocols. Abstract : Supplemental Digital Content is available in the text.